ANALYSIS AND FORECAST OF THE PRODUCTION PARAMETERS OF MAJOR CEREAL CROPS IN SERBIA - Novković, Nebojša (Journal on Processing and Energy in Agriculture, 2020)
This paper deals with the production parameters of major cereal crops in Serbia (namely the cultivation area, annual production and yields of the cereal crops considered) in the period 2005–2018. The objective of this study was to determine trends in and the volume and stability of the production parameters of the most important cereal crops in Serbia. Furthermore, a forecast of changes in the parameters observed was made for the five-year period 2019-2023. The following cereal crops were under consideration: corn, wheat, barley, oats, rye and triticale. The area devoted to corn in Serbia was found to be very stable, indicating a slight downward trend. However, the Serbian corn production lacked stability due to variations in yield, suggesting a very slight downward trend. Wheat was found to be far more stable with slightly growing trends in all the parameters considered. Moreover, positive trends in all the parameters considered were also noticed in the Serbian triticale production.
Keywords: cereals, areas, production, yields, Serbia